2014
DOI: 10.1021/la5002682
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary-Driven Motion of a Sessile Drop: Effect of Non-Monotonic Dependence of Surface Tension on Temperature

Abstract: ABSTRACT:We study the thermocapillary-driven spreading of a droplet on a nonuniformly heated substrate for fluids associated with a non-monotonic dependence of the surface tension on temperature. We use lubrication theory to derive an evolution equation for the interface that accounts for capillarity and thermocapillarity. The contact line singularity is relieved by using a slip model and a Cox-Voinov relation; the latter features equilibrium contact angles that vary depending on the substrate wettability, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 45 publications
0
69
0
2
Order By: Relevance
“…Savino et al (2013), and Hu et al Hu et al (2014) demonstrated that the use of these fluids within micro oscillating heat pipes led to an increase in the efficiency of these devices. In a slightly different context, it was very recently shown that the presence of a minimum in surface tension can also have a significant impact on the dynamics of the flow giving rise to very interesting phenomena such as the thermally induced "superspreading" (Karapetsas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Savino et al (2013), and Hu et al Hu et al (2014) demonstrated that the use of these fluids within micro oscillating heat pipes led to an increase in the efficiency of these devices. In a slightly different context, it was very recently shown that the presence of a minimum in surface tension can also have a significant impact on the dynamics of the flow giving rise to very interesting phenomena such as the thermally induced "superspreading" (Karapetsas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies involving horizontal and inclined substrates have shown that droplet motion is associated with the effect of contact-angle hysteresis and thermocapillary actuation. [43][44][45][46][47][48] These studies demonstrated the significant dependence of the contact angle on the induced surface-tension forces (Marangoni effect) and the deviation of the droplet's footprint from a circular shape. [43][44][45][46][47][48] Furthermore, wettability gradients induced by temperature gradients along a substrate have been found to influence the ensuing flows inside evaporating droplets.…”
mentioning
confidence: 87%
“…At x ¼ x 1 , the film thickness is fixed at h 0 ¼ 50 lm [Eq. (27)]. The pressure is fixed at the reservoir pressure…”
Section: B Contact Line Displacement Modelmentioning
confidence: 99%
“…14 Other techniques for droplet mobilization include substrate vibrations 15,16 or A.C. electrowetting. 17 Many authors have studied droplet actuation by means of thermocapillary stresses as a consequence of localized heating [18][19][20][21][22][23][24][25][26][27][28] and specifically the effect of thermocapillary stresses on the dynamics of the moving contact lines. [29][30][31][32][33][34][35][36] If either the driving force or the imposed speed exceeds a critical limit, commonly residual liquid is left behind on the substrate.…”
Section: Numerical Simulations I Introductionmentioning
confidence: 99%